Improving Istima’ and Kitabah Skills through Arabic Language Song Audio Media for Students of Class 1 MTsN 1 Kota Bima - Fika Nurhumaidah; Nur Hasaniyah; Abdul Muntaqim Al Anshory (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to improve students' listening and writing skills through the use of audio media in the form of Arabic songs in class 1 of MTsN 1 Kota Bima. The method used is Classroom Action Research (CAR) consisting of two cycles, where each cycle includes planning, implementation, observation, and assessment. The subjects involved in this study were a group of 30 students in class 1. The tools used include observation sheets, istima' tests, and writing assignments. The results of the study indicate that the use of Arabic songs as a learning tool can increase students' enthusiasm for learning and their understanding of vocabulary and grammar in Arabic. The purpose of this study was to investigate the relationship between Arabic songs and maharah istima' (listening skills), and to examine how effective the use of Arabic songs as a learning tool is in improving the istima' and kitabah skills of class 1 students of MTsN 1 Kota Bima. In addition, this study also aims to measure its impact on the understanding of vocabulary and sentence structure in Arabic. This type of research is a study that examines the relationship between variables using a numerical approach. The subjects studied in this study were students in grade 1 at MTsN 1 Kota Bima.